Magnetomotive optical coherence elastography for microrheology of biological tissues - Crecea, Vasilica (Society of Photo-Optical Instrumentation Engineers, 2013)
Optical coherence elastography (OCE) is an established paradigm for measuring biomechanical properties of tissues and cells noninvasively, in real time, and with high resolution. We present a different development of a spectral domain OCE technique that enables simultaneous measurements of multiple biomechanical parameters of biological tissues. Our approach extends the capabilities of magnetomotive OCE (MM-OCE), which utilizes iron oxide magnetic nanoparticles (MNPs) distributed and embedded in the specimens as transducers for inducing motion. Step-wise application of an external magnetic field results in displacements in the tissue specimens that are deduced from sensitive phase measurements made with the MM-OCE system. We analyzed freshly excised rabbit lung and muscle tissues. We observe that while they present some similarities, rabbit lung and muscle tissue displacements display characteristic differentiating features. Both tissue types undergo a fast initial displacement followed by a rapidly damped oscillation and the onset of creep. However, the damping is faster in muscle compared to lung tissue, while the creep is steeper in muscle. This approach has the potential to become a novel way of performing real-time measurements of biomechanical properties of tissues and to enable the development of different diagnostic and monitoring tools in biology and medicine.